Discrepancies between implicit and explicit self-concepts of intelligence: relations to modesty, narcissism, and achievement motivation - Gerstenberg, Friederike; Imhoff, Roland; Banse, Rainer; Schmitt, Manfred J. (Frontiers in Psychology, 2014)
Previous research has shown that different configurations of the implicit self-concept of intelligence (iSCI) and the explicit self-concept of intelligence (eSCI) are consistently related to individuals’ performance on different intelligence tests (Dislich, Imhoff, Banse, Altstötter-Gleich, Zinkernagel, & Schmitt, 2012). The results indicated that any discrepant configuration between the iSCI and the eSCI impairs performance. In the present study, how correspondence between the iSCI and the eSCI is related to intelligence test performance as well as personality traits of modesty (low eSCI, high iSCI), narcissism (high eSCI, low iSCI), and achievement motivation was investigated. Furthermore, a moderated mediation analysis showed that the relation between the iSCI-eSCI configurations and intelligence test performance was mediated by achievement motivation for modest individuals.